Preference Level and Iron Content of Analog Rice Combination of Seaweed Flour (Sargassum sp.) and Commercial Beneng Taro Flour - Aditia Mursyid Muhede; Sakinah Haryati; Rifki Prayoga Aditia (JURNAL PERIKANAN DAN KELAUTAN, 2024)
It is hoped that making analog rice from a combination of seaweed flour (Sargassum sp.) and commercial beneng taro can become an alternative food to overcome the problem of anemia in Indonesia. The aim of this research is to determine the best combination treatment for making analog rice based on the iron content and hedonic test. The experimental design used a completely randomized design with four combination treatments of seaweed flour (Sargassum sp.) and commercial taro beneng, namely: A (0%:100%), B (5%:95%), C (10%:90 %), and D (15%:85%). The results of the research showed that treatment C was the best treatment with the product hedonic level being preferred and had iron content of 4.13 mg/100 grams.